The results of the composite functions are:
Composite functions are functions that are obtained by combining two or more functions together
Assume that:
Then the computation of the composite functions are as follows:
[tex](f \times g)(x) = f(x) \times g(x)[/tex]
[tex](f \times g)(x) = (2x-3) \times (3x)[/tex]
[tex](f \times g)(x) = 6x^2-9x[/tex]
We have: [tex]f(x) = 2x - 3[/tex]
This gives
[tex]f(g(x)) = 2g(x) - 3[/tex]
So, we have:
[tex]f(g(x)) = 2(3x) - 3[/tex]
[tex]f(g(x)) = 6x - 3[/tex]
We have: [tex]g(x) = 3x[/tex]
This gives
[tex]g(f(x)) = 3f(x)[/tex]
So, we have:
[tex]g(f(x)) = 3(2x - 3)[/tex]
[tex]g(f(x)) = 6x - 9[/tex]
Read more about composite functions at:
https://brainly.com/question/10687170